A readout system for monolithic pixel sensor prototypes towards the upgrade of the ALICE Inner Tracking System. (1st January 2023) - Sarritzu, V.; ,
Abstract: The ALICE experiment at CERN is developing an innovative third iteration of the three innermost layers of the Inner Tracking System (ITS3) to be installed during the Long Shutdown 3 of the LHC (2026–28) [1]. Based on a commercial 65 nm CMOS imaging technology by TowerJazz [2], it consists of truly cylindrical wafer-scale sensors that can be installed as close as 18 mm to the interaction point. In order to validate the technology, several test chips were produced in a first submission named Multi-Layer Reticle 1 (MLR1). This contribution will describe the development, features, and performance of a custom test system for some of the prototypes in MLR1, namely Analogue and Digital Pixel Test Structures (APTS and DPTS, respectively) and pixel matrices with rolling shutter readout (CE65).